2020
DOI: 10.1021/acs.jnatprod.0c00288
|View full text |Cite
|
Sign up to set email alerts
|

Callicarpins, Two Classes of Rearranged ent-Clerodane Diterpenoids from Callicarpa Plants Blocking NLRP3 Inflammasome-Induced Pyroptosis

Abstract: Callicarpins A−D (1−4), possessing an unprecedented A-homoent-clerodane scaffold with a bicyclo[5.4.0]undecane ring system, and callicarpins E−G (5−7), with 5/6fused ent-clerodane diterpenoid skeletons, were isolated from Callicarpaarborea and C. integerrim. Their structures were elucidated by comprehensive spectroscopic data, X-ray crystal diffraction, chemical derivatization, and electronic circular dichroism (ECD) data. Putative biosynthetic pathways for these callicarpins are proposed. Compounds 2, 3b, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…Crystallographic analysis was performed according to previous procedures. , The data have been deposited at the Cambridge Crystallographic Data Centre with deposition nos. CCDC2016558, CCDC2016560, and CCDC2016561, which can be obtained free of charge from the Cambridge Crystallographic Data Centre via (or from the CCDC, 12 Union Road, Cambridge CB21EZ, U.K.; fax: + 44-1223-336-033; e-mail: deposit@ccdc.cam.ac.uk).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Crystallographic analysis was performed according to previous procedures. , The data have been deposited at the Cambridge Crystallographic Data Centre with deposition nos. CCDC2016558, CCDC2016560, and CCDC2016561, which can be obtained free of charge from the Cambridge Crystallographic Data Centre via (or from the CCDC, 12 Union Road, Cambridge CB21EZ, U.K.; fax: + 44-1223-336-033; e-mail: deposit@ccdc.cam.ac.uk).…”
Section: Methodsmentioning
confidence: 99%
“…Crystallographic analysis was performed according to previous procedures. 24,27 Antifungal and Antimicroalgal Assays. Antifungal evaluation against five phytopathogenic fungi (B. cinerea, C. miyabeanus, F. oxysporum f. sp.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…All non-hydrogen atoms were refined anisotropically with SHELXL-97 and SHELXL-2014 using full-matrix least-squares, and refinements of the H atoms in calculated positions were performed using a riding model. Molecular graphics were calculated with PLATON [37]. Crystallographic data have been deposited in the Cambridge Crystallographic Data Centre as CCDC 2,024,007 for 1.…”
Section: X-ray Crystallographic Analysismentioning
confidence: 99%
“…Terpenoids are abundant in medicinal plants and have a great potential to provide both novel structures and diverse biological activities. Phytochemical investigation has revealed that the genus Callicarpa is rich in diterpenes. Research on the chemical composition of C. bodinieri , C. arborea , C. rubella , and C. nudiflora has uncovered several types of terpenoids, such as clerodane and abietane diterpenoids, , some of which exhibited inhibitory anti-NLRP3 inflammasome activity and moderate inhibitory effects on spleen tyrosine kinase (SYK). The above-mentioned reports provide a theoretical basis for further studies on the diterpene of Callicarpa species.…”
mentioning
confidence: 99%